Histopatologi Hepatopankreas Udang Vannamei (Litopenaeus vannamei) Yang Terinfeksi White Spot Syndrome Virus (WSSV) - Sukerta, Made Ory; Julyantoro, Pande Gde Sasmita; Kartika, I Wayan Darya (Current Trends in Aquatic Science, 2025)
Controlling and monitoring fishery products, particularly vannamei shrimp, is important to reduce the risk of the spread of diseases and pathogens affecting vannamei shrimp. The samples of vannamei shrimp were obtained from 3 different shrimp farms in East Lombok, namely Labuan Haji village, Sambelia, and Kayangan. A total of 6 samples were collected, with 2 samples from Sambelia, 2 samples from Kayangan, and 2 samples from Labuan Haji. The aim of this research was to examine the suspected White Spot Syndrome Virus (WSSV) infection in shrimp using the Polymerase Chain Reaction (PCR) method and to determine the visual histopathological conditions of the infected organs, particularly the hepatopancreas. The extracted DNA from the shrimp's hepatopancreas was amplified using the PCR instrument, and the sample extracts were applied to gel electrophoresis to obtain a visual representation of the DNA bands. The bands were then analyzed semi-quantitatively using a UV transilluminator. Based on the visualization of the DNA bands from the vannamei shrimp extractions, it was found that out of the 6 tested samples, 2 were negative for White Spot Syndrome Virus (WSSV) infection, while 4 showed positive results indicating infection with White Spot Syndrome Virus (WSSV). These positive samples exhibited bands at around 941 bp. The visualization of cell damage could be observed through histopathological images, which revealed structural and morphological abnormalities in the affected hepatopancreas cells. The examination results indicated cell damage in the hepatopancreas, characterized by structural and functional changes in the infected cells due to White Spot Syndrome Virus (WSSV) infection.